Mathematical Communication Skills for Intermediate Stage Mathematics Teachers (Journal of the College of Basic Education, 2023)
The student is the owner of the direct relationship with the one who carries out the teaching process, so we see manyStudents prefer to study a specific content or course with a teacher over another, ifThey were given the opportunity to choose, and some of them may accept to study a specific specialization sometimes as soon asHis knowledge of a particular teacher is based on his teaching, and this is due to the idea that the student carries aboutThe teacher with regard to his teaching style and his skill in dealing with educational situations., 14) p. (233Among the basic skills in teaching are communication skills such as listening, speaking and acting.Their use usually by the teacher requires many activities to develop them and to know their impact onlearning, 13). p. (99Some educators assert that teaching skills, including clear writing of symbols,terminology, mathematical representations, clarity of discussions, asking questions, and listening toTheir answers differ in their communication with students according to different educational situations, but they agree that they areCommunication skills that track the student's understanding and questions, or is the understanding dependent on their use byThe teacher. 20, p. (111).The emergence of educational innovations and their increasing applications made the ambition to advance students.And make them at the level of mastery of scientific knowledge through the correction of reality and reorganization in the visiona new future, bearing in mind that the development of curricula in its broad sense is linked to a large extent with the preparation ofteachers and training them to organize their scientific experience, activities and teaching strategies because manySome of them still lack the necessary skills that qualify them to implement this vision.This means that knowledge of the mathematical communication skills that a teacher of mathematics possesses is necessary.Urgent that will enable him in the future to perform the requirements of teaching according to a standard that achieves the basic skillsFor the required activity according to the dimensions of the sports educational position and qualifying it, the two become at the level of